Investigation into the influence of flame retardant additives on some fire properties of polyester materials applying small-scale testing techniques - Półka Marzena; Gałaj, Jerzy; Karpovič, Zbignev (Journal of Civil Engineering and Management, 2013)
In order to investigate the impact of some inorganic additive flame retardants on the selected fire properties of the materials based on polyester resin Polimal 1033 APy, small-scale fire testing techniques have been used. Seven samples have been studied: unmodified PES, PES modified with MoO3 (7, 14 and 21 wt%) and PES modified with Sb2O3 (7, 14 and 21 wt%). The following flammable properties of materials have been determined: the heat of combustion (HOC), the ignition temperature of volatile thermal decomposition products (Tig), self-ignition temperature and oxygen index. A cone calorimeter method has been used for determining heat release rate (HRR), mass loss, specific extinction area (SEA) and other combustion parameters. The toxicological analysis of combustion products has been conducted. Based on the obtained results, the following conclusions have been made: (1) MoO3 and Sb2O3 added to the studied material change its flammable properties and fire parameters. It can be indicated by higher HOC, higher Tig and self-ignition temperature, as well as by lower HRR and SEA. Modified materials become safer in terms of fire hazard. (2) A significant reduction in HRRmax of approx. 40% in the content of 7 wt% has been observed. The lowest HRRmaxof approximately 300 kW/m2 and 450 kW/m2 have been obtained for 21 wt% in a range of 200–600 s at 30 kW/m2 and 100–400 s at 50 kW/m2 respectively. Except for a sample containing 7 wt% of Sb2O3, a clear local reduction in HRR (from 50 to 150 kW/m2), in case of all modified samples has been noticed. (3) Sb2O3 has a greater impact on the thermostability of the studied materials compared to MoO3 in all cases of heat flux density and additive concentrations. The effectiveness of Sb2O3, as a flame retardant is the most evident at 21 wt%.